IMPROVING INTEGRATED THEMATIC LEARNING PROCESS USING SCIENTIFIC APPROACH AT GRADE 3 ELEMENTARY SCHOOL - Zahratul Amalia; Riza Safriani; Delismita Pusra (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this study was to improve integrated thematic learning process through scientific approach at grade 3 elementary school. The subjects of this study were researchers as the teachers, and 22 students. This study applied PTK research. This study utilized a qualitative and quantitative approach. The results showed an increase in: (a) the average value of RPP in cycle I for 98% (A) and 100% (A) in cycle II, (b) the result of the learning process from teachers’ aspects in cycle I was 80% (B) and in cycle 2 was 95% (A), (c) the students’ aspects in cycle 1 was 51.59% (D) and in cycle II was 86.59% (A).